Imam Al-Ghazali on The Balance Observance of 'Ibadah (Devotional Act): An Enduring Legacy to The Muslim World - Mohd Rosmizi Abd Rahman (Universiti Sains Islam Malaysia, 2024)
This article analyses Imam al-Ghazali’s theory of the balance observance of ibadah (devotional acts or good deeds) among Muslims. Performing ‘ibadah, is part and parcel of the Muslims’ life. Nevertheless, the majority of Muslims—scholars and the public alike—place great emphasis only on the diligent outward performance of devotional acts, and on the observance of the outward requirements. However, Imam al-Ghazali goes beyond this normative practice, arguing that a mere outward observance of devotional acts is still insufficient, and indeed is still at risk. This article is theoretical in nature, and it involves bibliographic research, employing descriptive and analytic methods. The article founds that Imam al-Ghazali maintains devotional acts consist of outward and inward dimensions, and both need to be observed simultaneously and kept in balance. It is only through this balance observance that devotional acts will be transformed from mere physical motions of pure ritualistic observance to spiritually rich deeds, filled with real understanding, wisdom, and realisation.